The gremlins of grammar : - Boyle, Toni (McGraw-Hill, 2006)
lighthearted romp through the basics of American English that will help even the most grammatically challenged readers perfect their skills Do your participles dangle indelicately? Do you dare to split infinitives? Do you tremble at the thought of ending sentences with a preposition? Whether aspiring wordsmiths or avowed grammar geeks, readers will delight in this witty instructional that takes the bite out of American English. The Gremlins of Grammar offers a piquant primer for professionals, students, and anyone who wants to write it right and speak with style.